Adenosine Triphosphate and Synchronous Mitosis in Physarum polycephalum - Chin, B. (1968)
Synchronous mitoses occur in Physarum polycephalum in the absence of cell division. Nucleoside and nucleotide profiles were prepared from synchronously growing P. polycephalum at intervals throughout the growth cycle. Comparison of these profiles demonstrates that the pool of adenosine triphosphate decreases from a high level at prophase to a minimum through mitosis and increases again in the postmitotic period. These events appear to coincide with changes in the pools of adenosine diphosphate and adenosine but not with that of adenosine monophosphate. This observed decrease in the pool of adenosine triphosphate during mitosis was confirmed by direct enzymatic assay. These results presumably reflect the energy demands of the cell during mitosis.